Nembot Penganu Sebagai Kearifan Lokal Suku Paser Perspektif ‘Urf - Taufiqurrahman, Taufiqurrahman (De Jure: Jurnal Hukum dan Syari'ah, 2018)
‘Urf had emerged since being in the amid of Indonesian society long before Islam came, including the tradition of nembot penganu. This article aims to describe the process of carrying out the nembot penganu tradition in the traditional marriage of Paser tribe and to analyze the tradition of nembot penganu in perspective ‘urf. This research is empirical research with a qualitative approach. The results of this study indicate that the tradition of nembot penganu is a submission of various objects and money to prospective brides before the contract. The procession of the tradition is divided into saheeh urf and fasid urf. Submission of symbolic objects such as beras kuning, pandanus leaves and betel leaves including saheeh urf because it does not contain an element of polytheism. The procession of scattering beras kuning and coins includes as the fasid urf because it is over-attitude. Determination of nominal cash in the submission is considered as urf saheeh if it agrees with the willingness of men, and adjusts their abilities. Conversely, it becomes fasid urf if determined by the prospective bride's family and does not adjust the ability of the prospective bridegroom.‘Urf telah muncul sejak ditengah-tengah masyarakat Indonesia jauh sebelum Islam datang, termasuk di dalamnya tradisi nembot penganu. Artikel ini bertujuan untuk mendeskripsikan proses pelaksanaan tradisi nembot penganu dalam perkawinan adat Suku Paser dan menganalisis tradisi nembot penganu dalam perspektif ‘urf. Penelitian ini termasuk dalam penelitian empiris dengan pendekatan kualitatif. Hasil kajian ini menunjukkan bahwa tradisi nembot penganu merupakan pemberian benda dan uang  kepada calon mempelai perempuan sebelum akad. Prosesi dari tradisi tersebut terbagi dalam ‘urf shahih dan ‘urf fasid. Penyerahan benda-benda simbolis seperti beras kuning, daun pandan, dan sirih termasuk ‘urf shahih karena tidak mengandung unsur kemusyrikan. Prosesi penghamburan beras kuning dan uang logam termasuk ‘urf fasid karena bersifat sikap berlebih-lebihan. Penentuan nominal uang seserahan menjadi ‘urf shahih jika atas kerelaan pihak laki-laki, dan menyesuaikan kemampuanya. Sebaliknya, hal tersebut menjadi ‘urf fasid apabila ditentukan oleh keluarga calon mempelai perempuan dan tidak menyesuaikan kemampuan calon mempelai laki-laki.